Indian Commodity Derivatives Market : A Performance Review - Sonia (Indian Journal of Research in Capital Markets, 2023)
Purpose : The purpose of this study was to study the performance of Indiaâ€™s commodity derivatives market about the development of commodity exchanges, the number of commodities permitted to be traded, and the trade value. Methodology : This study was descriptive and exploratory. Most of the secondary data included in this paper was gathered from various sources, like newspaper articles, annual reports of the Forward Market Commission, reports of SEBI, research papers, and other resources. Findings : This article found out that the number of commodities available for futures trading increased to 113, and 15 commodity exchanges were working in India, including 11 regional and four national commodity exchanges. Trading in the commodity derivatives market eased down in 2020â€“2021 compared to previous years. Practical Implications : This paper desired to be a ready reckoner for future economists, policymakers, investors, hedgers, and researchers to analyze the performance of the commodity derivatives market. Originality : Since 2002â€“2003, the commodities market in India has undergone major changes, as indicated by the government’s development of three national commodity exchanges. India has had tremendous expansion in terms of commodity exchanges, the amount of commodities approved for futures trading, and the value and volume of transactions from 2002 to 2003.